1999
DOI: 10.2165/00003088-199937040-00001
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pharmacokinetics and Drug Metabolism of Tazarotene

Abstract: Tazarotene (AGN 190168) is a new acetylenic retinoid which is effective for the topical treatment of patients with stable plaque psoriasis and mild to moderate acne vulgaris. Topical gel application provides direct delivery of tazarotene into the skin. At 10 hours after a topical application of 0.1% tazarotene gel to the skin of healthy individuals and patients with psoriasis, approximately 4 to 6% of the dose resided in the stratum corneum and 2% of the dose distributed to the viable epidermis and dermis. Taz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
60
0
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(63 citation statements)
references
References 21 publications
1
60
0
2
Order By: Relevance
“…All of these studies mentioned investigated endocrinological effects of oral retinoid treatment. For topical retinoid treatment a low systemic bioavailability (<1%) after a single dose with increasing bioavailability after continuous treatment (up to 5.3%) was shown in a group of patients with psoriasis [8]. Experimental data suggests that percutaneous absorption rate is affected by state of the skin barrier, retinoid type, vehicle and dose [9].…”
Section: Discussionmentioning
confidence: 99%
“…All of these studies mentioned investigated endocrinological effects of oral retinoid treatment. For topical retinoid treatment a low systemic bioavailability (<1%) after a single dose with increasing bioavailability after continuous treatment (up to 5.3%) was shown in a group of patients with psoriasis [8]. Experimental data suggests that percutaneous absorption rate is affected by state of the skin barrier, retinoid type, vehicle and dose [9].…”
Section: Discussionmentioning
confidence: 99%
“…The systemic availability after topical tazarotene 0.05% or 0.1% gel is < 1% after single application, and 2.6% and 5.3%, respectively, after once-daily applications following 2 weeks of treatment. After 12 weeks of treatment, the systemic availability of tazarotene 0.05% was 1.8% and for the 0.1% tazarotene preparation it was 3.9% (Tang-Liu et al, 1999).…”
Section: Retinoidsmentioning
confidence: 97%
“…Following topical administration of tazarotene to healthy volunteers or patients with psoriasis or acne vulgaris, low but detectable plasma levels of tazarotenic acid can be measured (Tang-Liu et al, 1999). Oral tazarotene is currently in clinical development for the treatment of plaque psoriasis and acne.…”
mentioning
confidence: 99%
“…The rapid blood hydrolysis of tazarotene to the more water soluble tazarotenic acid is mediated by one or more paraoxon-inhibitable esterases (Madhu et al, 1997). In rat and human liver microsomes, the biotransformation of tazarotene was independent of cytochrome P450 (Tang-Liu et al, 1999). A recent pharmacokinetic study to assess the safety and dose proportionality of oral tazarotene found the main circulating agent, tazarotenic acid, was rapidly available in the systemic circulation with T max ranging from 2-to 3-h postdose (Tang-Liu et al, 1999).…”
mentioning
confidence: 99%
See 1 more Smart Citation